Relaxation processes in a week solution of cryocondensed water, heavy water and ethanol with nitrogen and argon - Drobyshev, A.; Aldiyarov, A.; Katpaeva, K.; Korshikov, E.; Kurnosov, V.; Sokolov, D.; Timchenko, A. (Recent Contributions to Physics, 2015)
Earlier studies of stability of ethanol molecules in nitrogen cryomatrix showed that the state of immobilized ethanol molecules in the matrix is not stable [1]. A slight increase of temperature of the matrix, long before its evaporation leads to a change in the vibrational spectra in a two-componentsolid solution of ethanol and nitrogen. This article considers the results of continued research in this direction.